Comparative analysis of the effects of real-time audio-visual feedback, yoga and pressure biofeedback stabilizer in core strengthening: a randomised controlled trial - Stephen Geovinson George; Mohanan Kamalakannan; Kandakurti Praveen Kumar; Mathukrishnan Ramprasad (Biomedical Human Kinetics)
Study aim: To compare the efficiency of a pressure biofeedback stabilizer (PBS), Riablo audio-visual feedback (RAV), and yoga in core strengthening exercise protocols in overweight individuals with trunk instability.